CAREGIVERS OF OLDER ADULTS DURING CARE TRANSITIONS: INSIGHTS INTO POSITIVE ASPECTS OF CAREGIVING. (16th November 2018) - Zakrajsek, A; Schuster, E; Wells, C; Williams, J; Silverchanz, P
Abstract: While family caregivers often play a vital role in supporting older adults transitioning from hospital to home, little is known about the caregiver experience during care transitions over time. This presentation will describe a pilot longitudinal study situated within a larger participatory action research project that examined the unique experiences of informal family caregivers of older adults in a care transition. Forty-five participants were recruited from two hospitals within a large regional health system and studied at three points in time: before hospital discharge, one week after discharge to home, and one month after discharge. Data were collected through online methods or mailed paper surveys and analyzed with descriptive statistics, Pearson bivariate correlations and paired t-tests. No significant changes were found in caregiver burden, caregiver responsibilities and competence in responsibilities, perceived social support, and quality of life. However, positive perceptions of caregiving relationship, perceived social support, and perception of health were significantly related to positive aspects of caregiving, as measured by a novel tool developed and tested in this study. This measure, the Positive and Enjoyable Aspects of the Caregiving Experience (PEACE) addressed role fulfillment, pride, gratitude, positive effects on other relationships, and personal meaning in the role of caregiver. High internal reliability (α=0.82) was found among PEACE constructs. Findings offer insights into longitudinal methodology with caregivers recruited from hospital settings as well as policy and program development to support caregivers in their role facilitating older adult care transitions from hospital to home.